Students' Perception towards the Teaching and Learning Process on Cause and Effect Sentences: A Study on 12th Grade Students of SMKN 2 Tebo - Rano, Regen; Safitri, Dian (Journal of English Language Teaching, 2024)
This study investigates the perceptions of 12th-grade students at SMKN 2 Tebo regarding the teaching methods used by their English teachers for mastering cause-and-effect sentences. Additionally, it explores the extent to which these methods contribute to students' improvement in identifying, interpreting, and using cause-and-effect sentences. The research employs a qualitative approach, specifically descriptive analysis, to analyze data collected through questionnaires and observations. The data analysis reveals that students perceive the teacher's teaching methods as lacking variety and engagement, leading to boredom and hindering their understanding of cause-and-effect sentences. Additionally, the study identifies a lack of motivation among students to learn more about cause-and-effect sentences. Based on the findings, the study concludes that the teacher's teaching methods need significant improvement to effectively engage students and enhance their understanding of cause-and-effect sentences. The study recommends incorporating more diverse and interactive teaching strategies to motivate students and improve their learning outcomes.